Cardiovascular inflammaging: mechanisms, consequences, and therapeutic perspectives - Spray, Luke; Richardson, Gavin; Haendeler, Judith; Altschmied, Joachim; Rumampouw, Valencia; Wallis, Sienna B.; Georgiopoulos, Georgios; White, Stephen; Unsworth, Amanda; Stellos, Konstantinos; Tual-Chalot, Simon; Spyridopoulos, Ioakim (Cell reports. Medicine, 2025)
Both aging and systemic inflammation are major risk factors for cardiovascular disease. This review summarizes the interrelationship of aging and inflammation—known as inflammaging—and the consequences for cardiovascular health. We discuss mechanisms including epigenetic modification, mitochondrial dysfunction, cellular senescence, and gut dysbiosis, many of which are themselves interrelated. Increasing understanding of inflammaging provides an array of biomarkers, some of which are now recommended in international guidelines. We also discuss therapeutic strategies aiming to modify the process of inflammaging and improve cardiovascular disease outcomes, either with immunomodulating agents or with therapies targeted at specific mechanisms, such as senolytics, telomerase activators, and pre- and probiotic supplementation. We conclude that inflammaging is a key part of cardiovascular aging and provides encouraging opportunities for new therapies.